The macroanatomic investigations on the formation of the cisterna chyli and thoracic duct in akkaraman sheep - Hakan Yalçın; Sadettin Tıpırdamaz; Kamil Beşoluk (Eurasian Journal of Veterinary Sciences)
In this study, formation of Ihe cisterna chyli and course and termination of the thoracic duct were mac-roscopically investigated. In this purpose, eight Akkaraman sheep were used. India ink were injected to various nodes of these animals. The thoracic duct originated from the cranial part ol the cisterna chyli and coursed dorsolateral^ of the thoracic aorta at the right of the median plane. At the fourth and lilth lumbar vertebra it inclines somewhat cra-nioventrally and passes to left side of the median plane. It was determined that the thoracic duct terminated lo the dorsolateral surface of the left external jugular vein at the level ol the first rib In this research, it was observed that the cisterna chyli is located sac-like, an elongated lymph reservoir at the ventral to large psoas muscle at the level of the second and third lumbar vertebra. Two small lymphatics joined together and formed lumbal trunks which opens to cisterna chyli. following a short courses At the level of the third lumbar vertebra, the cisterna chyli receives the lumbar, visceral and coliac. Visceral trunks is formed by the jejenal, intestinal and colic trunks. The celiac trunks is formed by the hepatic and gastric trunks.